2019
DOI: 10.1097/sla.0000000000002765
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preoperative Anticholinergic Medication Exposure With Postoperative Healthcare Resource Use and Outcomes

Abstract: Increasing ARS scores were associated with increased LOS, decreased survival, higher rates of institutional discharge and readmission, and higher costs of care. Perioperative interventional research to reduce the anticholinergic exposure in older surgical patients is likely warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…We found that frail patients had significantly higher rates of DBI and hyperpolypharmacy on discharge. Medication utilization has not been well‐studied in surgical populations but is important as it is linked to other adverse outcomes including geriatric syndromes 37,38 . Moreover, deprescribing interventions can be undertaken safely in the acute hospital setting to reduce the burden of potentially inappropriate medications, 39 although this needs to be confirmed in older hospitalized surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…We found that frail patients had significantly higher rates of DBI and hyperpolypharmacy on discharge. Medication utilization has not been well‐studied in surgical populations but is important as it is linked to other adverse outcomes including geriatric syndromes 37,38 . Moreover, deprescribing interventions can be undertaken safely in the acute hospital setting to reduce the burden of potentially inappropriate medications, 39 although this needs to be confirmed in older hospitalized surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unusual symptoms might result in more prescriptions and, indeed, probably more PIMs. This is the so-called prescribing cascade, whereby one medication is added to treat the symptom that arises from another medication (e.g., an antihypertensive therapy to treat hypertension from an NSAID) [24]. Having more PIMs may be a measure of underlying geriatric susceptibility [25].…”
Section: Discussionmentioning
confidence: 99%
“…Certain drugs are more frequently associated with adverse drug reactions, including digoxin, antidiabetic agents and non-steroidal anti-inflammatory drugs [ 26 ]. Specific classes of PIMs have also been associated with worse outcomes in hospitalised surgical patients [ 27 , 28 ]. The authors of the Beers criteria remind clinicians that the medications identified using the criteria are only potentially inappropriate, not always inappropriate [ 29 ].…”
Section: Discussionmentioning
confidence: 99%